Biochemical and molecular adaptation of rice plants towards low phosphate condition - Huong To, Thi Mai; Ha Chu, Hoang; Mai, Nga Thi Phuong (Academia Journal of Biology, 2022)
Rice is the staple food for half of the world’s population. Phosphorus is an essential element for rice plant growth, development and production; however, the availability of soluble phosphate for plant uptake is often limited due to the binding with cation in different pH environments. Therefore, the development of rice plant varieties, which can grow well under a limited phosphate environment, is an urgent need for agricultural development for biotechnology. This study reported two contrasting rice varieties’ biochemical and molecular adaptation toward a low phosphate medium. The results show that the response of these two varieties is genotype-dependent. We observed a higher phosphate use efficiency in the low-Pi-sensitive G299 rice variety than in the low-Pi-tolerant G22 rice variety. Moreover, the expression of five out of six investigated genes relating to the low Pi responsive pathway, including two purple acid phosphatase (PAP), phosphate starvation response 2 (PHR2), SPX (SYG1/PHO81/XPR1) domain-containing gene, phosphate transcription factor 1 (PTF1) and phosphate 1 (PHO1) were significantly higher in the low-Pi-sensitive accession than in the tolerant genotype. Impressively, 214 times more expression of the PHO1 was observed in the leaves of the G299 variety than in the G22 variety, followed by SPX, PTF1, PHR2, and PAP21 genes. Similarly, the PHO1 was induced at the highest level in the roots of the G299 variety, followed by PAP21, PHR2, PTF1, and SPX1 genes. These findings supply further information for elucidation of the mechanism behind the response of rice plants to low phosphate medium and the development of the low Pi nutrient happy rice varieties.